Evaluating the potential of three Fe- and Mn-(nano)oxides for the stabilization of Cd, Cu and Pb in contaminated soils - Michálková, Zuzana; Komárek, Michael; Šillerová, Hana; Della Puppa, Loïc; Joussein, Emmanuel; Bordas, François; Vaněk, Aleš; Vaněk, Ondřej; Ettler, Vojtěch (Journal of environmental management, 2014)
The potential of three Fe- and Mn-(nano)oxides for stabilizing Cd, Cu and Pb in contaminated soils was investigated using batch and column experiments, adsorption tests and tests of soil microbial activity. A novel synthetic amorphous Mn oxide (AMO), which was recently proposed as a stabilizing amendment, proved to be the most efficient in decreasing the mobility of the studied metals compared to nano-maghemite and nano-magnetite. Its application resulted in significant decreases of exchangeable metal fractions (92%, 92% and 93% decreases of Cd, Cu and Pb concentrations, respectively). The adsorption capacity of the AMO was an order of magnitude higher than those recorded for the other amendments. It was also the most efficient treatment for reducing Cu concentrations in the soil solution. No negative effects on soil microorganisms were recorded. On the other hand, the AMO was able to dissolve soil organic matter to some extent.
Keywords: Cadmium; Soil Pollutants; Environmental Pollution; kadmium; dekontaminace; látky znečišťující půdu; Manganese Compounds; těžké kovy; Humans; sloučeniny manganu; oxidy; adsorpce; Copper; Adsorption; lidé; měď; olovo; Decontamination; Oxides; Lead; znečištění životního prostředí; Metals, Heavy